Preliminary study of the miniaturization of lead (II) ion selective electrode based on thiourea derivatives - Viltres-Portales, Marcia; Lazo-Fraga, Ana Rosa; Díaz-García, Alicia; Plutín-Stevens, Ana María; Ramos-Cairo, Raúl (Revista Cubana de Química, 2017)
The present work reports the miniaturization of a solid-contact lead (II) ion selective electrode based on 1-benzoyl-3,3-diethylthiourea (BDE) as neutral carrier and tris-2-ethylhexilphosphate (TEHP) as mediator solvent in a polivynil chloride (PVC) matrix. Microelectrodes were prepared with glass capillaries of different diameters (2, 1 y 0,8 mm) and illustrates a good sensitivity to the metallic cation, with a slope close to a Nernstian logarithmic relationship for a divalent ion (29,53 mV/decade). Furthermore, the microelectrodes shows detection limits in order of 10-6 mol/L and a linearity range from 10-6 to 10-3 mol/L. These results are similar to reports for others sensors based on thiourea derivatives and even for commercial selective electrodes. Keywords: lead(II)-ion selective microelectrodes, 1-benzoyl-3,3-diethylthiourea.